A peptide resource for the analysis of Staphylococcus aureus in host–pathogen interaction studies. Issue 21 (7th September 2015) - Depke, Maren; Michalik, Stephan; Rabe, Alexander; Surmann, Kristin; Brinkmann, Lars; Jehmlich, Nico; Bernhardt, Jörg; Hecker, Michael; Wollscheid, Bernd; Sun, Zhi; Moritz, Robert L.; Völker, Uwe; et al.
<x xml:space="preserve">Abstract</x> Staphylococcus aureus is an opportunistic human pathogen, which can cause life‐threatening disease. Proteome analyses of the bacterium can provide new insights into its pathophysiology and important facets of metabolic adaptation and, thus, aid the recognition of targets for intervention. However, the value of such proteome studies increases with their comprehensiveness. We present an MS–driven, proteome‐wide characterization of the strain S. aureus HG001. Combining 144 high precision proteomic data sets, we identified 19 109 peptides from 2088 distinct S. aureus HG001 proteins, which account for 72% of the predicted ORFs. Peptides were further characterized concerning pI, GRAVY, and detectability scores in order to understand the low peptide coverage of 8.7% (19 109 out of 220 245 theoretical peptides). The high quality peptide‐centric spectra have been organized into a comprehensive peptide fragmentation library (SpectraST) and used for identification of S. aureus‐typic peptides in highly complex host–pathogen interaction experiments, which significantly improved the number of identified S. aureus proteins compared to a MASCOT search. This effort now allows the elucidation of crucial pathophysiological questions in S. aureus‐specific host–pathogen interaction studies through comprehensive proteome analysis. The S. aureus‐specific spectra resource developed here also represents an important spectral repository for SRM or for data‐independent acquisition MS approaches. All MS data have been deposited in the ProteomeXchange with identifier PXD000702 (http://proteomecentral.proteomexchange.org/dataset/PXD000702).